Diversity of Socio-Economic Develompent Countries and Regions of the World - a Macro Perspective - Knapińska, Magdalena (Studia Oeconomica Posnaniensia, 2017)
The aim of the study is to identify the diversity of socio-economic development in the world in some selected countries. Macroeconomic data such as GDP, GDP per capita and GDP growth, inflation and unemployment are presented. In addition, searching for the causes of this diversity presents the amount of investment and savings in the countries studied, as well as the level of HDI. The choice of countries was dictated primarily by geographical variations and curiosity research; therefore, there are a group of selected countries with different economies in different regions of the world. The test period covers the years 1990-2015, although there are also references to the beginning of the twentieth century.